Generic cardiology drug prices: the potential benefits of the Marc Cuban cost plus drug company model - Narendrula, Aparna; Lang, Jacob; Mossialos, Elias (Frontiers in Pharmacology, 2023)
This is a provisional file, not the final typeset article Introduction: Generic pharmaceuticals account for the majority of the 359 billion US pharmaceutical market, including for cardiology drugs. Amidst a lack of price transparency and administrative inefficiencies, generic drug prices are high, causing an undue burden on patients.Methods: We identified the 50 most used generic cardiology drugs by volume per the 2020 Medicare Part D spending data. We extracted cost per dose of each drug from the Marc Cuban Cost Plus Drug Company (MCCPDC) website and estimated the aggregate cost savings if MCCPDC were employed on a national scale by calculating the difference between this cost and Medicare spending.Results: Medicare spent 7.7 billion on the 50 most used generic cardiology drugs by volume in 2020 according to Medicare Part D data. Pharmacy and shipping costs accounted for a substantial portion of expenditures. Per our most conservative estimate, 1.3 billion (17% of total) savings were available on 16 of 50 drugs. A slightly less conservative estimate suggested 2.9 billion (38%) savings for 35 of 50 drugs.Discussion: There is enormous potential for cost savings in the US market for generic cardiology drugs. By encouraging increased competition, decreasing administrative costs, and advocating for our patients to compare prices between the MCCPDC and other generic pharmaceutical dispensers, we have the potential to improve access to care and corresponding outcomes for cardiology patients.